Human Rights: is the concept truly coherent with the Christian moral teaching? - Aleksander Stępkowski (Chrześcijaństwo-Świat-Polityka)
The text explores the evolution of anthropological perspectives within Christianity, specifically focusing on the concept of rights. It traces the historical shift from a pre-modern emphasis on the social nature of humans to the emergence of individualistic anthropology in the 17th century. The tension between freedom and justice becomes a central theme, with human rights seen as a means of protecting individual autonomy from social coercion. The text explores the concept of personhood in Christianity, emphasising its central role in understanding the Trinitarian identity of God and its significance in Christology. It examines the classical definition of a person  as an individual substance of reasonable nature, highlighting its limitations when applied to social aspects of human life. The author expresses scepticism about reconciling the concept of human rights with Christian anthropology, asserting that the rights-focused ethics is rooted in a non-Christian philosophical framework. The conclusion acknowledges the contemporary dominance of the rights-focused ethics but warns against the temptation to create a new "Christianity" compatible with this framework, urging a recognition of the anti-Christian nature of the ethical foundations of the modern Western society.